2004
DOI: 10.1002/chem.200305303
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis of Bimetallic Complexes with Three Halogeno Bridges

Abstract: Methods for the synthesis of bimetallic complexes in which two different metal fragments are connected by three chloro or bromo bridges are reported. The reactions are general, fast, and give rise to structurally defined products in quantitative yields. Therefore, they are ideally suited for generating a library of homo- and heterobimetallic complexes in a combinatorial fashion. This is of special interest for applications in homogeneous catalysis. Selected members of this library were synthesized and comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…The formation of this anion is rather unusual [24] given the thermodynamic stability of the [Cp*Rh(µ-Cl) 3 RhCp*] + cation, [11,25] and underlines the fact that the generation of [Cp*Ru(C 6 H 6 )] + is the driving force for the reaction. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of this anion is rather unusual [24] given the thermodynamic stability of the [Cp*Rh(µ-Cl) 3 RhCp*] + cation, [11,25] and underlines the fact that the generation of [Cp*Ru(C 6 H 6 )] + is the driving force for the reaction. …”
Section: Resultsmentioning
confidence: 99%
“…More recent investigations have shown that this method is quite general. [7,8] Mixed complexes with three halogeno-bridges can likewise be obtained in metathesis reactions [9,10] but alternative pathways such as ligand-transfer [11] or substitution [3a,3b,12] reactions have also been explored. [4] The various methods allow the synthesis of a structurally diverse set of homo-and heterobimetallic complexes in relatively short time.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have found that structurally related complexes with chelating 1,4-bis(diphenylphosphanyl)butane (dppb) or 1,4-bis(dicyclohexylphosphanyl)butane (dcypb) ligands instead of the two PPh 3 ligands can be synthesized (also in quantitative yield) using the aqua complex [(dppb)ClRu(m-Cl) 2 (m-OH 2 )RuCl(dppb)] (2) or the dinitrogen complex [(dcypb)(N 2 )Ru(m-Cl) 3 RuCl(dcypb)] (3) instead of 1. [4] The reactions depicted in Scheme 1 are general, fast, and give rise to structurally defined products in quantitative yields. Therefore, they are ideally suited to generate a library of homo-and heterobimetallic complexes in a combinatorial fashion.…”
mentioning
confidence: 99%
“…The synthesis of such complexes is easy and can even be performed in situ. [3,4] Furthermore, due to the high intrinsic reactivity of halobridged complexes, they are well suited as catalyst precursors. In the following, we describe two chloro-bridged Rh-Ru complexes, which act as highly active catalyst precursors for atom-transfer radical additions (ATRAs) of polyhalogenated compounds to olefins (the "Kharasch reaction").…”
mentioning
confidence: 99%
“…[3c] and 6 [4] or the dinuclear complex 7 [5] (Scheme 1). The related 1,4-bis(dicyclohexylphosphanyl)butane (dcpb) complex 10 was obtained by reaction of the dinitrogen complex 9 with [{(pcymene)RuCl 2 } 2 ].…”
Section: Introductionmentioning
confidence: 99%